The Effect of E-Learning on Students Learning Interest in the Equivalence Education Program - Shofwan, Imam; Aminatun, Siti; Handoyo, Eko; Kariadi, Mustasyfa Thabib (Journal of Nonformal Education, 2021)
The Equivalence Education Program is non-formal education that applies learning with the e-learning system to substitute conventional learning in formal education school. This study aims to identify and analyze (1) e-learning conducted by students, (2) students #39;interest in learning, and (3) the effect of e-learning on students#39; learning interest in the Package C Equivalence Program at PKBM Pioneer Karanganyar. The method used is a quantitative approach focusing on the ex post facto approach. The research sample was 45 students of Package C at PKBM Pioneer Karanganyar, out of a total population of 141 Package C students. The data were collected using questionnaire and documentation. The analysis technique used is statistical and inferential analysis techniques focusing on simple linear regression analysis techniques. The results showed that (1) Package C students at PKBM Pioneer Karanganyar appreciated that the e-learning was equivalent to online learning (2) Package C students at PKBM Pioneer Karanganyar had high learning interest, (3) there was a positive influence and e-learning was significant for students#39; interest in learning in the Package C Program at PKBM Pioneer Karanganyar. The benefit of this research is to provide an overview of online learning that is fun to students.